Estimating Fmsy from an ensemble of data sources to account for density dependence in Northeast Atlantic fish stocks. (15th October 2020) - Sparholt, Henrik; Bogstad, Bjarte; Christensen, Villy; Collie, Jeremy; van Gemert, Rob; Hilborn, Ray; Horbowy, Jan; Howell, Daniel; Melnychuk, Michael C; Pedersen, Søren Anker; Sparrevohn, Claus Reedtz; Stefansson, Gunnar; et al.
Abstract: A new approach for estimating the fishing mortality benchmark F msy (fishing pressure that corresponds to maximum sustainable yield) is proposed. The approach includes density-dependent factors. The analysis considers 53 data-rich fish stocks in the Northeast Atlantic. The new F msy values are estimated from an ensemble of data sources: (i) applying traditional surplus production models on time-series of historic stock sizes, fishing mortalities, and catches from the current annual assessments; (ii) dynamic pool model (e.g. age-structured models) estimation for stocks where data on density-dependent growth, maturity, and mortality are available; (iii) extracts from multispecies and ecosystem literature for stocks where well-tested estimates are available; (iv) the "Great Experiment" where fishing pressure on the demersal stocks in the Northeast Atlantic slowly increased for half a century; and (v) linking F msy to life history parameters. The new F msy values are substantially higher (average equal to 0.38 year −1 ) than the current F msy values (average equal to 0.26 year −1 ) estimated in stock assessments and used by management, similar to the fishing pressure in the 1960s, and about 30% lower than the fishing pressure in 1970–2000.